Does Education Cause Spiritual Belief Change? - Donald Thomas Markle (Arizona State University, 2012)
Currently, little is known about the influence classroom learning has on the spiritual beliefs of students.  Despite this fact, decisions on educational policy, parental home schooling, and even whether to bring legal actions against school districts, often rest on the assumption that education can induce spiritual belief change.  To begin the process of filling the current gap in academic knowledge, this qualitative interview study centers on the personal accounts of educational and religious histories of sixteen participants.  The interview data collected suggests that education has a limited role in beginning the process of spiritual belief change, but that education is often relied on once an episode of belief revision begins to occur.  Instead, major life events, such as the death of a family member, were often described as being the catalyst for spiritual belief change.  The importance of emotion in both education and belief change is discussed.